2021
DOI: 10.1007/s43441-021-00355-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on Horizon Scanning with a Focus on the Development of AI-Based Medical Products: Citation Network Analysis

Abstract: Horizon scanning for innovative technologies that might be applied to medical products and requires new assessment approaches to prepare regulators, allowing earlier access to the product for patients and an improved benefit/risk ratio. The purpose of this study is to confirm that citation network analysis and text mining for bibliographic information analysis can be used for horizon scanning of the rapidly developing field of AI-based medical technologies and extract the latest research trend information from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Figure 1 gives an outline of the citation network analysis process which has been published in references ( 16 , 17 , 20 ). We converted the citation network into an unweighted network, with papers as nodes and citation relationships as links.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 gives an outline of the citation network analysis process which has been published in references ( 16 , 17 , 20 ). We converted the citation network into an unweighted network, with papers as nodes and citation relationships as links.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is highly sensitive to certain terms; when text mining is used with other methods, the problem of terminological distortion will be unignorable. Therefore, we propose an objective methodology for horizon scanning that identifies cutting edge technology to be applied to medical products, which are AI-based medical devices, drugs related to T cell immune responses, and extracellular vesicle-based products from all research papers in the target field using both citation network analysis methods and text mining ( 16 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that the analysis of the interdisciplinary fields is characterized by the distribution of articles in clusters of their basic technologies, which differs from AI-based medical products and immunology fields [ 12 , 13 ]. When applying horizon scanning based on the citation network analysis to an interdisciplinary research field confirming the development of the product or medical technology under consideration and evaluating not only the research trends in nonclinical studies toward clinical application but also trends in basic technologies that constitute the product or medical technology is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This index is calculated for each cluster by applying term frequency inverse document frequency (TFIDF), which is an index used for each document. This method has been used in past analyses [ 12 15 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation